Randomized controlled trial protocol: A quanti-quali approach for analyzing the results of an intervention on the waiting list for bariatric surgery - Evangelista, Mayara Martins [UNESP]; Crisp, Alex Harley; Rossato, Sinara Laurini [UNESP]; Vieira, Carla Maria [UNESP]; Bossa, Rayli; Oliveira, Maria Rita Marques de [UNESP] (Pontificia Universidade Catolica Campinas, 2019)
Objective This article aims to describe the protocol of a randomized clinical trial and the baseline results of the study of a one-year interdisciplinary intervention in users of the public health system in the bariatric surgery waiting list. Methods A randomized, single-blind clinical trial will be conducted including 88 participants recruited on an outpatient clinic of the public health system. Participants were randomized into the control group (n=44), receiving the usual treatment; and into the intervention group (n=44), participating in the educational intervention. Participants had their food intake, negative affectivity and physical inactivity/sedentary behavior assessed, as well as anthropometric and body composition measurements; their blood samples were collected; and also had different physical capacity tests. Results Of the 157 participants invited, 27 had severe functional limitations, one was under-age, and four declined the study due to associated diseases. Eighty-eight participants were randomized: 44 for the Control Group and 44 for the Intervention Group. When comparing the demographic and biochemical characteristics, there were no differences between groups except for serum glucose (GC=110.4 +/- 46.8 mg/dL and GI93.1 +/- 16.9 mg/dL, p=0.039). Conclusion This study protocol describes the methodology used in the study of educational intervention for the promotion of health care of patients on the waiting list for bariatric surgery. It shows that there is similarity between the baseline comparison groups. Registro Brasileiro de Ensaios Clinicos (Brazilian Clinical Trials Registry), RBR-775y3d.
Keywords: Bariatric surgery; Clinical trial; Obesity; Public Health System